2012
DOI: 10.1371/journal.pone.0032176
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Genetic Variants in Alcohol Deydrogenases, and Risk of Cardiovascular Diseases: A Prospective Study and Meta-Analysis

Abstract: ObjectiveFirst, to investigate and compare associations between alcohol consumption and variants in alcohol dehydrogenase (ADH) genes with incidence of cardiovascular diseases (CVD) in a large German cohort. Second, to quantitatively summarize available evidence of prospective studies on polymorphisms in ADH1B and ADH1C and CVD-risk.MethodsWe conducted a case-cohort study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam cohort including a randomly drawn subcohort (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…36 Alcohol has acute and chronic effects that are mostly dose-dependent 37 and reversible with abstinence or reduced intake. 38 Different genetic, 39,40 ethnic, 41,42 and behavioural 14,43 susceptibility factors influence the degree of damage. Repair mechanisms involving hypertrophy and a degree of myocyte regeneration can, to some extent, counteract the generation of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…36 Alcohol has acute and chronic effects that are mostly dose-dependent 37 and reversible with abstinence or reduced intake. 38 Different genetic, 39,40 ethnic, 41,42 and behavioural 14,43 susceptibility factors influence the degree of damage. Repair mechanisms involving hypertrophy and a degree of myocyte regeneration can, to some extent, counteract the generation of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…These alcohol-attributable costs exceed 1% of the gross national product of high-and middle-income countries, making pathological alcohol use one of the largest avoidable risk factors for the global burden of disease [1]. Studies have reported that alcohol use is associated with cardiovascular disease (CVD), although there is debate about these conclusions [2][3][4][5][6][7][8]. However, there is the lack of updated information that specifically examines the status of alcohol consumption in China, which has been experiencing rapid economic progress and epidemiologic transitions that are often associated with an increase in CVD [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…, Stella Trompet senior researcher 11 , Andrew Wong senior study manager 12 , Alana Cavadino statistician 13 , Dagmar Drogan scientist 14 , Sandosh Padmanabhan reader 15 , Shanshan Li postdoctoral research fellow 16 , Ajay Yesupriya health scientist 17 , Maarten Leusink doctoral candidate 18 , Johan Sundstrom senior epidemiologist 19 , Jaroslav A Hubacek senior scientist 20 , Hynek Pikhart senior lecturer 21 , Daniel I Swerdlow clinician scientist 1 , Andrie G Panayiotou lecturer in public health 22 , Svetlana A Borinskaya leading researcher 23 , Chris Finan bioinformatician 1 , Sonia Shah postdoctoral research fellow 24 , Karoline B Kuchenbaecker research associate in genetic epidemiology 25 , Tina Shah postdoctoral research fellow 1 , Jorgen Engmann data manager 1 , Lasse Folkersen postdoctoral research fellow 26 , Per Eriksson professor of cardiovascular medicine 26 , Fulvio Ricceri epidemiologist, research fellow 28 , Olle Melander professor 27 , Carlotta Sacerdote medical epidemiologist 28 , Dale M Gamble researcher 29 , Sruti Rayaprolu researcher 30 , Owen A Ross associate professor 30 , Stela McLachlan data manager 31 , Olga Vikhireva research associate 21 , Ivonne Sluijs assistant professor 32 , Robert A Scott senior investigator scientist 9 , Vera Adamkova head of department 33 , Leon Flicker professor of geriatric medicine 34 , Frank M van Bockxmeer director of cardiovascular genetics laboratory 35 , Christine Power professor of epidemiology and public health 13 , Pedro Marques-Vidal associate professor of internal medicine 36 , Tom Meade emeritus profe...…”
mentioning
confidence: 99%